Safety and Efficacy of Anti-CD19-Chimeric Antigen Receptor T Cell Combined With Programmed Cell Death 1 Inhibitor Therapy in a Patient With Refractory Post-Transplant Lymphoproliferative Disease: Case Report and Literature Review - Feng, Gang; Li, Qing; Zhu, Haibo; Jiang, Yanyu; Yuan, Jijun; Fu, Yingxin; Deng, Qi (Frontiers in Oncology, 2021)
Post-transplant lymphoproliferative disease (PTLD) often exhibits poor prognosis and high mortality, and there are no uniform guidelines for the treatment of this disease. Anti-CD19 chimeric antigen receptor (CAR) T cells show significant efficacy in treatment of relapse/refractory diffuse large B-cell lymphoma (DLBCL). Treatment using anti-CD19-CAR T-cell therapy in PTLD has been limited by immunosuppressants and has not been widely employed. In this study, a refractory post kidney transplant DLBCL patient with a high tumor burden was enrolled in a clinical trial of anti-CD19-CAR T-cell therapy. The tacrolimus dose was not decreased during combination chemotherapy, as the creatinine level of the patient increased. To improve the function of autologous T cells, combination therapy with anti-CD19-CAR T cells and programmed cell death 1 (PD-1) inhibitors was selected. After treatment with the combination therapy, the patient was diagnosed with grade 1 cytokine release syndrome and grade 3 immune effector cell-associated neurotoxicity syndrome. The amplification peak of anti-CD19-CAR T cells reached 9.01% on day 7. With PD-1 inhibitor maintenance therapy, his disease was maintained in partial remission for 18 weeks. However, his tumor suddenly increased in size, and he discontinued the treatment, including radiation therapy. The anti-CD19-CAR T cell and PD-1 inhibitors have a combined effect on PTLD, and this combination therapy needs to be further explored.